Hepatitis B Vaccination Impact and the Unmet Need for Antiviral Treatment in Blantyre, Malawi . (9th November 2021) - Stockdale, Alexander J; Meiring, James E; Shawa, Isaac T; Thindwa, Deus; Silungwe, Niza M; Mbewe, Maurice; Kachala, Rabson; Kreuels, Benno; Patel, Pratiksha; Patel, Priyanka; Henrion, Marc Y R; Bar-Zeev, Naor; et al.
Abstract: Background: Hepatitis B is the leading cause of cirrhosis and liver cancer in sub-Saharan Africa. To reduce mortality, antiviral treatment programs are needed. We estimated prevalence, vaccine impact, and need for antiviral treatment in Blantyre, Malawi. Methods: We conducted a household study in 2016–2018. We selected individuals from a census using random sampling and estimated age-sex-standardized hepatitis B surface antigen (HBsAg) seroprevalence. Impact of infant hepatitis B vaccination was estimated by binomial log-linear regression comparing individuals born before and after vaccine implementation. In HBsAg-positive adults, eligibility for antiviral therapy was assessed. Results: Of 97386 censused individuals, 6073 (median age 18 years; 56.7% female) were sampled. HBsAg seroprevalence was 5.1% (95% confidence interval [CI], 4.3%–6.1%) among adults and 0.3% (95% CI, .1%–.6%) among children born after vaccine introduction. Estimated vaccine impact was 95.8% (95% CI, 70.3%–99.4%). Of HBsAg-positive adults, 26% were HIV-positive. Among HIV-negative individuals, 3%, 6%, and 9% were eligible for hepatitis B treatment by WHO, European, and American hepatology association criteria, respectively. Conclusions: Infant HBV vaccination has been highly effective in reducing HBsAg prevalence in urban Malawi. Up to 9% of HBsAg-positive HIV-negative adults are eligible, but have an unmet need, for antiviral therapy. Abstract : In a large census-based community serosurvey in Blantyre, Malawi adult HBsAg prevalence was 5.1%, and 0.3% among vaccine-eligible children. Estimated vaccine impact was 95.8% (95% CI, 70.3%–99.4%). Up to 9% of HBsAg-positive adults had an unmet need for antiviral treatment.